1984
DOI: 10.1111/j.1464-410x.1984.tb05381.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum and Upper Urinary Tract Stones

Abstract: The occurrence of bacteria and Ureaplasma urealyticum in the upper urinary tract was studied in 50 patients operated on for renal stones. Cultures were performed on voided urine, pelvic urine obtained during surgery and the stone. The chemical composition of the stones was analysed. Twenty-six stones were of metabolic origin and 24 infection-induced, i.e. composed of struvite and/or carbonate-apatite. Ureaplasma urealyticum was cultured from the upper urinary tract in 1 patient with metabolic stones, and in 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 19 publications
(15 reference statements)
0
14
0
2
Order By: Relevance
“…Urease activity is essential for the colonization of the gastric mucosa by Helicobacter pylori and colonization of the urinary tract by both Proteus mirabilis and Staphylococcus saprophyticus (20,25,30). In addition, urease is thought to play a central role in the pathogenesis of Ureaplasma urealyticum urinary and respiratory tract infections (27,35).…”
Section: Vol 186 2004 Global Gene Expression In S Aureus Biofilms mentioning
confidence: 99%
“…Urease activity is essential for the colonization of the gastric mucosa by Helicobacter pylori and colonization of the urinary tract by both Proteus mirabilis and Staphylococcus saprophyticus (20,25,30). In addition, urease is thought to play a central role in the pathogenesis of Ureaplasma urealyticum urinary and respiratory tract infections (27,35).…”
Section: Vol 186 2004 Global Gene Expression In S Aureus Biofilms mentioning
confidence: 99%
“…These organisms are frequently present in the lower urinary tract and our results support the hypothesis that they occasionally can colonize the upper urinary tract in a retrograde fashion. We have demonstrated in humans that ureaplasmas can reach and colonize and subse quently form stones in the upper urinary tract [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental stud ies have shown that inoculation of U. urealyticum into the rat bladder results in the formation of bladder stones [6] despite the fact that it has not been possible to recul ture the organism from the stone, or the bladder [7, 8J. In contrast, M. hominis is not urease-producing and has not been incriminated with stone formation clinically or experimentally [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Urate sind nicht zu verwechseln mit den Harnsäurekonkrementen, welche sich im sauren Milieu bei Urin-pH-Werten von <6,0 bilden. Die Ausbildung von Struvit ist aufgrund gemeinsamer prädisponierender Faktoren oft mit der Mineralisation von Karbonatapatit [Dahlit, Ca 10 (PO 4 ,CO 3 ) 6 (OH,CO 3 ), radiologisch schattengebend, relative Häufigkeit von 4,8-32,5%[2,23]] vergesellschaftet[12]. Beide Minerale werden häufig als Mischkomponenten in einem Harnstein beobachtet.Während Struvitsteine pathognomonisch für das Vorhandensein eines HWI sind, ist das Auftreten von Karbonatapatitsteinen ohne Struvit als Mischkompo-…”
unclassified